2020
DOI: 10.1101/2020.06.02.130336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clustering-mediated activation of Cdc42 GTPase antagonized by GAPs in fission yeast

Abstract: The small GTPase Cdc42 is critical for cell polarization in eukaryotic cells. In rod-shaped fission yeast Schizosaccharomyces pombe cells, active GTP-bound Cdc42 promotes polarized growth at cell poles, while inactive Cdc42-GDP localizes ubiquitously also along cell sides. Zones of Cdc42 activity are maintained by positive feedback amplification involving the formation of a complex between Cdc42-GTP, the scaffold Scd2 and the guanine nucleotide exchange factor (GEF) Scd1, which promotes the activation of more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…However, after division, Cdc42 activation at the cell ends requires both removal of Rga4 from the cell ends and MOR activation. A recent preprint has shown that presence of the GAPs at the cortex prevents Cdc42 activation at those sites even when the scaffold Scd2, which recruits Scd1 to the cortex, localizes to those sites (Lamas et al, 2020b). Another preprint suggests that Cdc42 GAP levels in daughter cells determine the pattern of polarized growth in those cells (Pino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after division, Cdc42 activation at the cell ends requires both removal of Rga4 from the cell ends and MOR activation. A recent preprint has shown that presence of the GAPs at the cortex prevents Cdc42 activation at those sites even when the scaffold Scd2, which recruits Scd1 to the cortex, localizes to those sites (Lamas et al, 2020b). Another preprint suggests that Cdc42 GAP levels in daughter cells determine the pattern of polarized growth in those cells (Pino et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Polarized Cdc42 activation depends on Ras1 GTPase, which promotes polarized localization of the Cdc42 GEF Scd1 (Chang et al, 1994;Chen et al, 2019;Lamas et al, 2020b). However, ras1Δ mutants continue to display the PrESS phenotype after recovery from LatA treatment (Supplementary figure S3B).…”
Section: A Candidate Screen To Identify Cell-cycle-dependent Regulatomentioning
confidence: 99%